CLASSIFICATION OF BIODEGRADABLE POLYMERS - I. I. Karpunin (Nauka i Tehnika, 2015)
The executed investigations have made it possible to ascertain that a morphological structure of starch granules mainly determine technological peculiarities of starch isolation from raw material, its modification and its later use. Morphological structure of starch granules primarily depends on type of plant starch-containing raw material which has been used for its isolation. Class of raw material exerts a strong impact on the shape and size of the granules. Linear “light” amylose chains and “heavy” amylopectin branch chains form a starch granule ultrastructure. X-ray research has proved that starch granules are characterized by presence of interlacing amorphous and crystalline regions. In this case polymer orientation using stretching of the obtained end product influences on its physical and mechanical  indices which are increasing due to polymer orientation. For the purpose of packaging orientation of polymer films can solve such important problems as significant improvement of operational properties, creation of  thermosetting film materials, improvement of qualitative indices of the recycled film.Results of the conducted research have proved the fact that it is necessary to make changes in technology in order to increase biological degradability of the recycled packaging made from polymers and improve physical and mechanical indices. In this regard film production technology presupposes usage of such substances as stark and others which are characterized by rather large presence of branch chains of molecules and interlacing amorphous and crystalline regions. Such approach makes it possible to obtain after-use package which is strong and quickly degradable by micro-organisms.